Rare bs - decays in the covariant quark model (International Journal of Mathematics and Physics, 2014)
Considering the surge of great interest to the problem of CP violation recently observed in a Bs  Bs system,decays of Bs to D  D and color suppressed decay Bs → J/ψ φ attracted the attention of both theorists andexperimentalists. We find new values for the covariant quark model parameters (with built-in infrared confinement)in the meson sector by fitting the leptonic decay constants and a number of electromagnetic decays, and then evaluatein a parameter-free way the form factors of B(Bs) → P(V) transitions within an entire kinematic range of themomentum transfer. Our results are applied to calculating the widths of nonleptonic Bs decays to, * * S S S S S S DD D D  DD  and * *S S D D  . The largest contribution to ΔΓ for s s B  B system comes from these modes. Thenonleptonic decay Bs → J/ψφ is also considered. Though this decay mode is color suppressed it has importantimplications in the search for possible CP-violating novel physics effects in s s B  B mixing.